Making glassy solids ductile at room temperature by imparting flexibility into their amorphous structure. Issue 10 (3rd October 2018) - Fan, Zhao; Ding, Jun; Ma, Evan
ABSTRACT: Making glasses ductile at room temperature is a daunting challenge, but has been shown to be feasible in recent years. We explain the plastic flow from the standpoint of the flexibility available in the amorphous structure: imparting flexibility into the structure facilitates bond switching needed to mediate shear transformations to carry strain. This structure–property correlation is demonstrated using molecular dynamics simulation data. The flexibility can be improved via ultrafast quench or rejuvenation. In particular, the flexibility volume parameter offers a quantitative metric to explain the flexibility and deformability, even for glasses where the commonly cited free volume is not applicable. GRAPHICAL ABSTRACT: Impact Statement: This Perspective demonstrates using examples and models that it is the flexibility rather than the excess volume that can be tuned to facilitate plastic flow and ductility in glassy materials.